Impact of a Mobile Health Application on Medication Adherence, Thyroid Function, and Quality of Life in Patients with Hypothyroidism: A Prospective Comparative Study - Saima Askari; Eraj Abbas; Azra Shaheen; Mahwish Bano (Pakistan Journal of Medical Sciences, 2026)
Background & Objective: Effective hypothyroidism management requires consistent daily levothyroxine therapy; poor adherence causes fluctuating Thyroid Stimulating Hormone (TSH), persistent symptoms, and long-term complications. To evaluate the impact of a mobile application on symptom improvement and clinical outcomes through improved treatment adherence among patients with hypothyroidism. Methodology: The study was conducted at the Outpatient Department of Diabetes & Endocrine center, Karachi over a duration of 10 months from 1st January 2025 to 31st October 2025. A total of 60 participants were included and divided into two groups: Group-1 (Control), did not use the mobile application, and Group-2 (Test), which used the mobile application. Patients aged 18 to 60 years with a confirmed diagnosis of hypothyroidism requiring ongoing levothyroxine therapy were included. Patients with hyperthyroidism, thyroid cancer, thyroid nodules or severe comorbidities were excluded. Symptoms (weight gain, cold intolerance, increased sleepiness, menstrual irregularity), TSH levels and Quality of Life Scale (WHOQOL), were assessed at baseline, after two and six months in both groups. Results: Mobile app users showed lower mean TSH levels (4.0 ± 2.10 mIU/L) than non-users (6.78 ± 2.78 mIU/L; p < 0.001) and higher quality-of-life scores (82.43 ± 18.25 vs. 72.10 ± 21.64; p